DOES LOCAL CURRENCY SETTLEMENT ENHANCE EXCHANGE RATE STABILITY?EVIDENCE FROM INDONESIA - Nabillah Hidayat; Ni Putu Wiwin Setyari (Adisam Publisher, 2025)
Indonesia's dependence on the United States Dollar in international trade poses a significant threat to the stability of the Rupiah exchange rate. To reduce reliance on the U.S. Dollar, Bank Indonesia introduced the Local Currency Settlement (LCS) policy in collaboration with four partner countries: Malaysia, Thailand, Japan, and China. This study aims to analyze the impact of Local Currency Settlement implementation (D1), exports (X1), imports (X2), and inflation rate (X3) on the probability of Rupiah exchange rate stability. The research employs a logistic regression method and utilizes secondary data spanning the period from 2012 to 2023. The findings indicate that the implementation of Local Currency Settlement increases the likelihood of an unstable Rupiah exchange rate compared to the pre-implementation period. Exports contribute to a higher probability of Rupiah exchange rate stability. Conversely, imports and inflation rates increase the likelihood of exchange rate instability.